K2S2O8-mediated metal-free direct C–H functionalization of quinones using arylboronic acids. Issue 12 (28th October 2015) - Ilangovan, Andivelu; Polu, Ashok; Satish, Gandhesiri
Abstract : Direct C–H functionalization of quinones with arylboronic acids is achieved using K2 S2 O8 as the sole and efficient green catalytic system. Abstract : Direct C–H functionalization of quinones with arylboronic acids is achieved using K2 S2 O8 as the sole and efficient green catalytic system. This method provides a straightforward and sustainable way to construct arylquinones via a radical pathway in moderate to good yields under metal-free conditions.